Middle Miocene bottom water carbonate clumped isotope and Mg/Ca temperatures, ODP Site 122-761B, Indian Ocean - Modestou, Sevasti; Leutert, Thomas Jan; Fernandez, Alvaro; Lear, Caroline H; Meckler, Anna Nele (PANGAEA, 2020)
The middle Miocene is an important analogue for potential future warm climates. Unfortunately, relatively few independent deep ocean temperature records exist, though these are required for climate model validation and estimates of changes in ice volume. The few existing records suggest that bottom water temperatures were 5 – 8°C warmer than present. In order to improve confidence in proxy data, we generated a new bottom water temperature record using carbonate clumped isotopes (Δ47) and compared our results with Mg/Ca-based estimates for the deep Indian Ocean at ODP Site 761. Our Δ47 temperature record agrees well with previously published Mg/Ca temperatures for this site, predicting average deep-sea temperatures of 11.0 ± 1.7°C during the middle Miocene Climatic Optimum (MCO, 14.7 – 17 Ma), 8.1 ± 1.9°C after the middle Miocene Climate Transition (MCT, 13.0 – 14.7 Ma) and a cooling across the MCT of 3 ± 2°C (uncertainties 95% confidence level). The Mg/Ca record derived from the same samples indicates a very similar magnitude of cooling of ~ 2°C. Examining non-thermal factors that could bias either paleothermometer, changes in saturation state are the most likely cause for any remaining offsets, with the caveat that, over the majority of the record, the Mg/Ca temperatures are within the 95% confidence intervals of the Δ47 temperatures. Our new Δ47 temperature record implies a ~0.6 ‰ seawater δ18O change over the MCT, again in good agreement with Mg/Ca-derived estimates. As previously suggested, both paleothermometers imply a heavier than modern seawater δ18O composition after the MCT. It consists of final calculated bottom water temperatures based on carbonate clumped isotope compositions (Δ47) and metal ion (Mg, Li, Ca) ratios. The raw and intermediate carbonate clumped isotope data used to produce the Δ47 temperatures is archived with the EarthChem database, linked under related datasets or at the url: https://doi.org/10.26022/IEDA/111523 . The raw element/metal concentration data are from Lear et al., 2010.